Alice's adventures in Wonderland - Carroll, Lewis, 1832-1898 (Sterling Pub., 2005)
Presents an illustrated edition of the classic tale of Alice as she falls down a rabbit hole and discovers a world of amusing, nonsensical characters. Includes review questions.